The Model for Development of Successful Textile Industry - Sawangrat, Nilawan (Journal of Roi Kaensarn Academi, 2023)
Objectives: 1) To study the general management of textile industry; 2) To study the factors of the model for development of successful textile industry; and 3) To develop a model of structural formula of the model for development of successful textile industry. This is a quantitative research. The sample groups consist of 500 entrepreneurs or business managers in textile industry; while 250 samples are from mid-size and small-size industry, and 250 samples are from big-size industry. Statistics uses are descriptive, inferential, and multiple regression statistics. The research results reveal that: 1) The general management of textile business industries stretch from 10-20 years manufacturing goods for sale within the country, and the sources of funds used to support businesses are from banks or financial institutions; 2) Analysis results of the significant levels of the factors of the model for development of sucessful textile industry. In general, the significant level is at a high level. And when individual factors are taken into account, all factors are rated the significance at a high level; of which technology factor is the highest, second to that is marketing factor, follow by organizational resources factor, and organizatinal success, in that order; and 3) Analysis results of the developed model of structural formula reveal that the possibility value of Chi-Square Distribution is equal to 0.158, the value of Relative Chi-Square is equal to 1.220, the Conformity Index Value is equal to 0.960, and the Root Mean Square Error of Approximation value is equal to 0.016, considered passed according to evaluation criteria, and in consistent and in coherent to the empirical data.